Intracellular Trafficking Network and Autophagy of PHBHHx Nanoparticles and their Implications for Drug Delivery - Sun, Xiangyu (Sci Rep, 2019)
3-hydroxybutyrate-co-3-hydroxyhexanoate (PHBHHx), which is naturally generated by biodegradable polyhydroxyalkanoates synthesized by bacteria, is an attractive material for drug delivery due to its controllable physical properties, non-toxicity, environmental friendliness, degradable properties and good biocompatibility. However, the intracellular trafficking network pathways, especially the autophagy mechanism of PHBHHx nanoparticles (NPs), have rarely been investigated. In this paper, we successfully prepared the NPs used solvent displacement method and investigated the autophagy pathways and other intracellular trafficking mechanisms based on NPs with the assistance of Rab proteins. We found that NPs were internalized in cells mainly via clathrin endocytosis and caveolin endocytosis. Beside the classical pathways, we discovered two new pathways: the micropinocytosis early endosome (EEs)-micropinocytosis-lysosome pathway and the EEs-liposome-lysosome pathway. NPs were delivered to cells through endocytosis recycling vesicles and GLUT4 exocytosis vesicles. Similar to other nanoparticles, NPs also induced intracellular autophagy and were then degraded via endolysosomal pathways. 3-MA and CQ were used as autophagy inhibitors to avoid the degradation of NPs through lysosomes by blocking endolysosomal pathways. Tumor volumes and weights were significantly decreased when autophagy inhibitors and chemical drugs packaged in NPs were cooperatively used.